Phases of the moon: as simple as ABCDE teaching the phases of the moon to first graders using patterns. (18th October 2022) - Blum, Caleigh; Taylor, Amy
Abstract: Children are very curious about the world around them. You may find them peering at tadpoles in a pond, counting ants on a log, or wondering about the stars, the sun, and the moon. I have been asked many times: Is the moon really made of cheese? Do astronauts live on the moon? Why does the moon look different every time I look up? Introducing young learners to our universe, beyond what their eyes can see, is a powerful teaching moment that primary teachers like myself get the pleasure to experience. Fostering students' early curiosities regarding our universe is one of the first steps to opening their minds to the vision of endless possibilities. Making observations, asking questions, and recognizing patterns are a few of the initial skills a young science learner should be encouraged to practice. In this particular unit, first grade students make observations of the sky including the differences in features and apparent movement of celestial objects. This unit and the featured lesson emphasize the use of students' prior knowledge and observations of the sky and identifying patterns to predict and infer how the moon changes during the lunar cycle.